Genetic Variation in the Feeding Behavior of Isofemale Lines of Nesidiocoris tenuis - Chinchilla-Ramírez, Milena; Pérez-Hedo, Mertixell; Pannebakker, Bart A.; Urbaneja, Alberto (mdpi, 2020)
Zoophytophagous predators provide biocontrol services in various major crops of modern horticulture due to the combination of its predatory capacity and the induction of plant defenses derived from its phytophagy. However, under certain conditions of prey scarcity, these natural enemies can inflict plant damage. Exploitation of genetic variation and subsequent selective breeding on foraging traits is a potential alternative to overcome this inconvenience. In this study, we quantified the genetic variation of phytophagy and zoophagy of Nesidiocoristenuis (Reuter) (Hemiptera: Miridae), a zoophytophagous predator widely used in tomato crops to suppress key pests. We compared nine isofemale lines on their capacity to produce necrotic rings and wilting on tomato plants as a proxy for phytophagy, as well as their efficacy to prey on Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs, as a proxy for zoophagy. Differences between isofemale lines in phytophagy and zoophagy indicated a genetic basis. Variation found in the zoophagy levels was larger than that in phytophagy levels. Our results showed that there is a genetic basis for the variation observed in the feeding behavior of isofemale lines of N.tenuis, highlighting the potential importance of selective breeding for such traits of biocontrol interest